2011
DOI: 10.1097/mnm.0b013e32834bf262
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of scintigraphic rapid gastric emptying

Abstract: Upper gastrointestinal symptoms have a poor clinical specificity to the actual rate of gastric emptying on scintigraphy. Diarrhoea as a symptom does not appear to be associated frequently with RGE, but our results confirm its relationship with hypoglycaemia. The majority of patients with a rapid emptying on gastric-emptying scintigraphy have no identifiable cause for an accelerated motility. Scintigraphic gastric-emptying studies provide a reliable and noninvasive method of investigation in patients where conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…3,10,28 In another study, 28% of 642 patients undergoing scintigraphy had rapid GE, perhaps because a less stringent criterion was used to define rapid GE (ie, gastric half-emptying time less than 70 minutes). 29 Nearly, one-third of patients with rapid GE1 had nausea and/or vomiting, perhaps because rapid delivery of nutrients distends and Only insulin therapy* 89 (59) 9 (33)…”
Section: Discussionmentioning
confidence: 99%
“…3,10,28 In another study, 28% of 642 patients undergoing scintigraphy had rapid GE, perhaps because a less stringent criterion was used to define rapid GE (ie, gastric half-emptying time less than 70 minutes). 29 Nearly, one-third of patients with rapid GE1 had nausea and/or vomiting, perhaps because rapid delivery of nutrients distends and Only insulin therapy* 89 (59) 9 (33)…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing recognition that rapid gastric emptying may occur not only in diabetes mellitus or after fundoplication but also in patients with functional diarrhea, functional dyspepsia, and autonomic dysfunction (917) We have observed that some patients with rapid early gastric emptying (e.g., at 30 or 60 minutes) have a normal gastric emptying t 50 probably because the emptying rate slows after the initial rapid phase. It is conceivable that early (i.e., at 15, 30, and 60 minutes) and late (i.e., at 240 minutes) postprandial breath samples will increase the accuracy of the GEBT for identifying rapid and delayed gastric emptying relative to scintigraphy respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective cohort of 642 patients with presumed gastroparesis and RGE, the correlation between symptoms and GET were only 62% and 29%, respectively. 18 Some studies even report a preponderance of RGE over gastroparesis in non-specific symptoms. In a small 57 patient trial exploring gastric emptying in patients with functional dyspepsia, RGE was more common (21%) than delayed gastric emptying of solids (13%).…”
Section: Discussionmentioning
confidence: 99%
“…19 Our study supports prior studies reporting the poor correlation between clinical symptomatology and the diagnosis of gastroparesis. 17,18 This study did not look at response of tGES to pain, except as part of a larger symptoms spectrum. However, a recent report did examine pain, in relation to neuropathic changes in the GI tract, and found that some patients with abdominal pain do respond well to tGES.…”
Section: Discussionmentioning
confidence: 99%